Adjunct prednisone in community-acquired pneumonia: 180-day outcome of a multicentre, double-blind, randomized, placebo-controlled trial - Claudine A. Blum; Eva A. Roethlisberger; Nicole Cesana-Nigro; Bettina Winzeler; Nicolas Rodondi; Manuel R. Blum; Matthias Briel; Beat Mueller; Mirjam Christ-Crain; Philipp Schuetz (BMC Pulmonary Medicine, 2023)
Abstract Background Several trials and meta-analyses found a benefit of adjunct corticosteroids for community-acquired pneumonia with respect to short-term outcome, but there is uncertainty about longer-term health effects. Herein, we evaluated clinical outcomes at long term in patients participating in the STEP trial (Corticosteroid Treatment for Community-Acquired Pneumonia). Methods This predefined secondary analysis investigated 180-day outcomes in 785 adult patients hospitalized with community-acquired pneumonia included in STEP, a randomised, placebo-controlled, double-blind trial. The primary endpoint was time to death from any cause at 180 days verified by telephone interview. Additional secondary endpoints included pneumonia-related death, readmission, recurrent pneumonia, secondary infections, new hypertension, and new insulin dependence. Results From the originally included 785 patients, 727 were available for intention-to-treat analysis at day 180. There was no difference between groups with respect to time to death from any cause (HR for corticosteroid use 1.15, 95% CI 0.68 to 1.95, p = 0.601). Compared to placebo, corticosteroid-treated patients had significantly higher risks for recurrent pneumonia (OR 2.57, 95% CI 1.29 to 5.12, p = 0.007), secondary infections (OR 1.94, 95% CI 1.25 to 3.03, p = 0.003) and new insulin dependence (OR 8.73, 95% CI 1.10 to 69.62, p = 0.041). There was no difference regarding pneumonia-related death, readmission and new hypertension. Conclusions In patients with community-acquired pneumonia, corticosteroid use was associated with an increased risk for recurrent pneumonia, secondary infections and new insulin dependence at 180 days. Currently, it is uncertain whether these long-term adverse effects outweigh the short-term effects of corticosteroids in moderate CAP. Trial registration This trial was registered with ClinicalTrials. gov, number NCT00973154 before the recruitment of the first patient. First posted: September 9, 2009. Last update posted: April 21, 2015.